Polygraph Survey and Evaluation Based on Analytic Hierarchy Process - Zhixia Jiang; Yibo Liu; Pinchao Meng (Institute of Advanced Engineering and Science, 2014)
The analytic hierarchy process (AHP) is a kind of combining quantitative analysis and qualitative analysis of comprehensive evaluation method. In modern personality test, lying is a common phenomenon. This paper combined with the actual survey results, using AHP to measure the process of empowerment, in fact is through the hierarchy model is set up as index system, the subjective indicators of two comparison and evaluation, through the judgment matrix to calculate the weight coefficient of every index. After through the consistency check, corresponding to hiring and personality assessment to empowerment in school keep file, in order to obtain better truth, accuracy, so as to realize are established for the big five personality test scores, to a certain extent, to avoid lying, better more authenticity of the test results.